Implementation of oral health evidence-based practices in early care education settings across the U.S. during different COVID-19 periods - Phoebe P. Tchoua; Shreena Patel; Aviva Shira Starr; Richard Rairigh; Falon Smith; Erik A. Willis (PLoS ONE, 2025)
The COVID-19 pandemic disrupted oral health practices in early care education (ECE) centers. This study describes the implementation of oral health evidence-based practices (EBP) in ECE centers enrolled in the web-based Go NAPSACC program pre-, during-, and post-COVID-19 stay-at-home (SAH) orders. This repeated cross-sectional study analyzed retroactive data from three types of programs (n = 1,490), that participated in Go NAPSACC oral health modules between January 2017 and April 2024: Head Start (n = 154), family child care home (FCCH; n = 540), and center-based (n = 796). Programs that did not use the Oral Health module (n = 10,425) and had duplicate registrations (n = 91) were excluded. The analysis focused on EBP total score and percentage of EBP met scores. We found significant differences in oral health EBP total and EBP met scores between program type (p < 0.001). Head Start programs had statistically significant higher EBP total percentage scores (81.8, 95% confidence interval [CI] = 78.5, 85.2; p < 0.0001) than FCCH programs (69.5, 95% CI = 67.1, 71.8; p < 0.0001), and center-based programs (59.5, 95% CI = 57.3, 61.7). Similarly, Head Start programs had higher EBP met scores (62.0, 95% CI = 57.7, 66.3; p < 0.0001), than FCCH programs (49.7, 95% CI = 46.7, 52.7; p < 0.0001), and center-based programs (36.9, 95% CI = 34.1, 39.8). We observed no statistically significant differences among programs based on SAH order period for neither EBP total scores (period, p = 0.761; interaction between program type and period, p = 0.788) nor EBP met scores (period, p = 0.178; interaction between program type and SAH order period, p = 0.293). These findings suggest that ECE programs struggle to meet oral health EBP across the three study periods, and the observed differences across program type was not explained by SAH orders.